Sublethal influences of Azadirachta indica on the developmental stages of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Gurpreet, S; Anureet, K C; Avneet, K; Jawala, J (Plant Science Today, 2026)
This research investigated the sublethal and antifeedant effects of three different neem-based formulations on the development of the fall armyworm, Spodoptera frugiperda, a major pest of maize. The study was conducted under controlled laboratory conditions to ensure consistency and reliability of results. The tested formulations included a commercially available neem product, neem oil and neem seed kernel extract (NSKE). Second instar larvae of S. frugiperda were exposed to sublethal concentrations of each formulation and various biological and developmental parameters were closely monitored. These included larval and pupal durations, pupal weight, adult emergence rate, adult body size and adult longevity. The findings revealed that all three neem-based treatments significantly influenced these developmental traits compared to the control. Among the treatments, the commercial neem formulation had the most pronounced effects, notably prolonging both larval and pupal stages while simultaneously reducing pupal weight, adult emergence, adult size and lifespan. These disruptions in development suggest that neem-based products, particularly commercial formulations, have considerable potential as environmentally friendly tools in integrated pest management (IPM) programs. Their use could help to suppress S. frugiperda populations by impairing their development and reproductive capacity, offering a sustainable alternative to conventional chemical insecticides in maize cultivation.